Factors Affecting Capital Expenditure Allocation: Empirical Evidence from Regency/City Government in Indonesia - Ilham Maulana Saud; Eka Asterina; Gisti Fairuz Trisha (Universitas Muhammadiyah Yogyakarta, Indonesia, 2020)
Research aims: To analyze the effect of local taxes, regional retribution, special allocation fund, and area size on the allocation of capital expenditure with economic growth as a moderating variable in the regency/city Governments in Indonesia from 2016 to 2017.Design/Methodology/Approach: This study used secondary data obtained through the website of the Ministry of Home Affairs, Ministry of Finance, and Audit Board of the Republic of Indonesia. Based on the purposive sampling method, a sample of 565 regencies/cities in Indonesia was obtained. The hypothesis testing in this study used Moderated Regression Analysis.Research findings: Based on the results of the study, it could be concluded that partially the local tax variables, special allocation fund, and area had a positive and significant effect on capital expenditure allocation. In contrast, regional retribution variables did not affect capital expenditure allocation, and economic growth could moderate the effect of local tax on capital expenditure allocation, but unable to moderate the effect of regional regional on capital expenditure allocations.Theoretical contribution/Originality: This research proved the theory of fiscal federalism in the relationship to fiscal decentralization, such as local taxes, economic conditions, public services, and public welfare. Moreover, this study enriched the literature on the application of the theory of stewardship in government agencies.Practitioner/Policy implication: Regional governments in regencies/cities in Indonesia are expected to explore the potential of their regions better so that they can improve the steward function to the community.Research limitation/Implication: The research period was relatively short; due to the availability of data only from 2016 to 2017, many research data were outliers. Future research is expected to renew the observation period and change the intervening model, as well as add other variables related to capital expenditure, such as General Allocation Funds (DAU), Revenue Sharing Funds (DBH), population numbers, Budget Surplus (SILPA) and others.